“Dosis de fertilización en la producción de pepino (cucumis sativus L.) variedad market more 76, con sistema de espalderas en Lamas” - Ynoue Menooza, Carlos Enrique (2008)
With the purpose of determining doses effect of NPK fertilizer, on agronomic parameter of cucumber under the trellis system in conditions of Lamas, town in the San Martín Region and to determine the economic analysis of the studied treatments applying statistical outlining with blocks completely at random and employing the dose of NPK fertilizer, T1 (202-65-381), T2 (120-50-50), T3 (180-120-240) and T4 as a witness without application, it was applied dose of fertilization in the cucumber production (Cucumis sativus L.), Market More 76 variety, in soil with organic matter 2,94% and 5,23 pH in which was evaluated the following parameters, plant length, number of branches, number of fruit per plant at harvest, length of the harvest fruits, fruit diameter at harvest, weight of fruit to harvest and economic analysis of the used treatments. Treatments Ta and T 1 won longest plant with 2, 72 and 2, 71 meters and a biggest number of branches with branches 10,5 and 9,87; T1, Ta and T2 won greater length fruit with 21,46; 21,36 and 20,93 centimeters; Ta, T2 and T1 treatments won greater diameters with 5,54; 5,52, and 5,52 centimeters; Ta, T1 and T2 treatments won highest values with 403,91; 391,75 and 382,4 grams regarding to the witness without fertilization which won 343,38 grams; T1 and T2 treatments obtained the largest number of fruit with 5,3 and 4,9 fruits per plant on average. T1 treatment obtained the highest yield, with 106428 kilograms per hectares and the highest net value of production (NPV) with SI. 37345,57 and a cost benefit relation 2,20 and T4 won less yield with 66027,50 kilograms per hectares and a lower cost benefit of production with S/. 15255,56 and a lower cost benefit relation with 1, 12. Key words: Cucumis sativus L, cucumber, fertilization, NPK dose, nitrogen, phosphorus, potassium.